Necessity is the mother of invention avoidance motivation stimulates creativity through cognitive effort.. [article]. - Roskes, Marieke
Compared with approach motivation, avoidance motivation has often been related to reduced creativity because it evokes a relatively inflexible processing style. This finding seems inconsistent with the dual pathway to creativity model, which poses that both flexible and persistent processing styles can results in creative output. Reconciling these inconsistencies, the authors hypothesized that avoidance-motivated individuals are not unable to be creative, but they have to compensate for their inflexible processing style by effortful and controlled processing. Results of 5 experiments revealed that when individuals are avoidance motivated, they can be creative as when they are approach motivated, but only when creativity is functional for goal achievement, motivating them to expert the extra effort (Experiments 1-4). The authors found that approach motivation was associated with cognitive flexibility and avoidance motivation with cognitive persistence (Experiment 1), that creative tasks are perceived to be more difficult by avoidance-than by approach-motivated individuals, and that avoidance-motivated individuals felt more depleted after creative performance (Experiments 2a, 2b, and 3). Finally, creative pe4rformance of avoidance-motivated individuals suffered more from a load on working memory (Study 4). The present results suggest that for people focusing on avoiding negative outcomes, creative performance is difficult and depleting, and they only pay these high cognitive costs when creativity helps achieving their goals.-(from the authors)
Keywords: Creativity; Approach; Motivation; Avoidance; Depletion